PENGEMBANGAN LEARNING MANAGEMENT SYSTEM (LMS) MENGGUNAKAN MOODLE PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMA - Febriani, Silvia; Nofri Hendri; Septriyan Anugrah; Elsa Masriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the unavailability of innovative technology-based learning media at SMA Negeri 1 Kubung. Despite having adequate digital infrastructure, the school has not optimally utilized its resources for Informatics learning. This study aims to develop a Learning Management System (LMS) using Moodle as a learning medium for Class X Informatics subject at SMA Negeri 1 Kubung that is valid, practical, and effective. This study is a Research and Development (R&D) study using the 4D development model from Thiagarajan, consisting of four stages: define, design, develop, and disseminate. The research subjects were 26 students of class X.2. Research instruments included validation questionnaires, practicality questionnaires, and pretest-posttest items. Results showed that: (1) the LMS development was systematically carried out through four 4D model stages; (2) LMS validity was rated as "Very Valid" by media and material experts; (3) LMS practicality was rated as "Very Practical" by students and teacher; and (4) the effectiveness test showed an average N-Gain score of 0.71 (71.12%) categorized as High. Thus, the Moodle-based LMS developed is feasible for use as Class X Informatics learning media at SMA Negeri 1 Kubung.